Technological change and societal growth analyzing the future - Coakes, Elayne, 1950-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book provides a practical and comprehensive forum for exchanging research ideas and down-to-earth practices which bridge the social and technical gap within organizations and society at large"--Provided by publisher.
1. Exploring meaning: the implications of a hyphen for socio-technical theory and practice / Elayne Coakes and Jim Coakes -- 2. Designing visionary leadership teams / Martin Johnson -- 3. The change equation / Peter Duschinsky -- 4. Leveraging communities for sustainable innovation: a commentary / Elayne Coakes, Peter Smith and Dee Alwis -- 5. Affective factors for successful knowledge management / Peter Smith -- 6. Identifying competences in IT professionals through semantics / Ricardo Colomo-Palacios ... [et al.] -- 7. Think global, act local: how ICTs are changing the landscape in community development / Sylvie Albert and Don Flournoy -- 8. Towards a knowledge-based economy - the case of Botswana: a discussion article / Bwalya Kelvin Joseph -- 9. A framework for analyzing online communities: sponsor and member value proposition / M. Gordon Hunter and Rosemary Stockdale -- 10. Realising virtual reality: a reflection on the continuing evolution of new media / Allan McLay -- 11. Free, open, online help forums: convenience, connection, control, comfort, and communication / Carla van de Sande -- 12. A way out of the information jungle: a longitudinal study about a socio-technical community and informal learning in higher education / Isa Jahnke -- 13. The diverging effects of social network sites on receiving job information for students and professionals / Bart Rienties ... [et al.] -- 14. Performing Charlotte: a technique to bridge cultures in participatory design / Ann Light ... [et al.] -- 15. Achieving best practice manufacturing involving tacit knowledge through the cautious use of mixed-mode modeling / Miles G. Nicholls and Barbara J. Cargill.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 23, 2012).
Keywords: Technological innovations; Organizational change; E-government; Democracy; Technological change; Empowerment; Team development; HRM; Knowledge sharing; Humanistic redesign; Technological politics; Implementation; Change and technology; Human factors and operational efficiency; Information systems development; Knowledge management systems; Knowledge sharing; Learning organizations; Electronic books